Differences in the temporal trends of childhood overweight and obesity in Spain in the 2011-2019 period by sex, age and socioeconomic level: results of the ALADINO study - Enrique Gutiérrez-González; Blanca Andreu-Ivorra; Almudena Rollán-Gordo; Laura Tejedor-Romero; Francisco Sánchez-Arenas; Marta García-Solano (Elsevier, 2024)
Introduction: Childhood excess weight is a growing public health problem. The aim of this study was to assess temporal trends in the prevalence of overweight, obesity and central obesity in schoolchildren aged 6-9 years in Spain between 2011 and 2019 based on demographic and socioeconomic characteristics. Methodology: The analysis included data from the 2011, 2015 and 2019 rounds of the cross-sectional observational and descriptive ALADINO study in schoolchildren of both sexes aged 6-9 years. We conducted a descriptive analysis of the trends in the prevalence of overweight and obesity (defined according to the criteria of the World Health Organization and the International Obesity Task Force) and of central obesity, in addition to associated demographic and socioeconomic variables. Results: Between 2011 and 2019, the prevalence of overweight (WHO criteria) decreased in boys aged 6, 7 and 8 years (by −5.4%, −5.7% and −5.3%, respectively) and boys whose parents had a higher educational attainment (by −5.3%). In relation to the socioeconomic level, overweight in boys declined at all income levels. However, between 2011 and 2019, both the prevalence of overweight in girls and the prevalence of obesity (applying the WHO and IOTF criteria) and the prevalence of central obesity in both sexes remained stable. Conclusions: The prevalence of overweight and the prevalence of obesity in schoolchildren aged 6-9 years in Spain remain high. Between 2011 and 2019, the prevalence of overweight in children aged 6-8 years and in children whose parents had university degrees decreased, whereas obesity in boys, overweight and obesity in girls and central obesity in both sexes remained stable. Resumen: Introducción: El exceso de peso infantil es un problema de salud pública creciente. El objetivo del trabajo es estudiar la evolución de la prevalencia de sobrepeso, obesidad y obesidad central en escolares de 6 a 9 años en España entre 2011 y 2019 según características demográficas y socioeconómicas. Metodología: Se incluyeron las rondas 2011, 2015 y 2019 del estudio observacional, descriptivo y transversal ALADINO en escolares de ambos sexos de 6 a 9 años. Se realizó un análisis descriptivo de la evolución de la prevalencia de sobrepeso y obesidad según los criterios de la Organización Mundial de la Salud (OMS) y la International Obesity Task Force (IOTF), así como obesidad central, y las variables demográficas y socioeconómicas asociadas. Resultados: Entre 2011 y 2019 se redujo la prevalencia de sobrepeso (critrerios OMS) en niños de 6, 7 y 8 años (−5,4, −5,7 y −5,3 puntos porcentuales respectivamente) y niños cuyos progenitores tenían estudios superiores (−5,3 puntos porcentuales). Por renta, el sobrepeso en niños se redujo en todos los niveles de ingresos. Sin embargo, entre 2011 y 2019, se mantuvieron estables tanto la prevalencia de sobrepeso en niñas como la prevalencia de obesidad según las referencias OMS e IOTF y la de obesidad central en ambos sexos. Conclusiones: Las prevalencias de sobrepeso y obesidad en escolares de 6 a 9 años en España siguen siendo altas. Entre 2011 y 2019 disminuyó la prevalencia de sobrepeso en niños de 6 a 8 años y aquellos cuyos progenitores tienen estudios universitarios, mientras que la obesidad en niños, el sobrepeso y la obesidad en niñas, y la obesidad central en ambos sexos han permanecido estables.